1990
DOI: 10.1111/j.1432-1033.1990.tb19104.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional NMR studies on des‐pentapeptide‐insulin

Abstract: The shortened analogue of insulin, des-(B26 -B30)-pentapeptide insulin, has been characterized by twodimensional 'H NMR. The 'H resonance assignments and the secondary structure in water solution are discussed. The results indicate that the secondary structure in solution is very similar to that reported for the crystalline state. A high flexibility of both A and B chains is observed. Of the two conformations seen in the 2-Zn insulin crystals and indicated as molecules 1 and 2 (Chinese nomenclature), the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…As pointed out previously, des-(B26 -B30)-insulin is a rather flexible molecule [25]. When it is dissolved in 'H,O, all amide protons exchange rapidly with the solvent.…”
Section: Local Mobilitymentioning
confidence: 64%
See 3 more Smart Citations
“…As pointed out previously, des-(B26 -B30)-insulin is a rather flexible molecule [25]. When it is dissolved in 'H,O, all amide protons exchange rapidly with the solvent.…”
Section: Local Mobilitymentioning
confidence: 64%
“…We shall compare the NMR structure with molecules 1 and 2 in the porcine insulin X-ray structure and its own averaged crystal structure from an RMD trajectory. Our previous results [25] suggested that the protein appears to be rather flexible, on the basis of the sensitivity of the chemical shifts to changes in temperature and pH. This conclusion is reinforced by analysis of the NOES.…”
Section: -___mentioning
confidence: 77%
See 2 more Smart Citations
“…We and others have recently described the two-dimensional NMR resonance assignment of a monomeric insulin analogue, des-pentapeptide-(B26-B30)-insulin (DPI) (1,2), which provides a favorable system for NMR studies due to reduced aggregation (3). DPI retains sufficient structural information for proper function and folding (4)(5)(6)(7)(8)(9)(10)(11)(12)(13), and its crystal structure is similar to the corresponding portion ofthe intact protein (6,7).…”
mentioning
confidence: 99%